2014
DOI: 10.1055/s-0034-1370898
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Correction of Scoliosis in Children with Spastic Quadriplegia: Benefits, Adverse Effects, and Patient Selection

Abstract: Study Rationale Cerebral palsy (CP) is a group of nonprogressive syndromes of posture and motor impairment associated with lesions of the immature brain. Spastic quadriplegia is the most severe form with a high incidence of scoliosis, back pain, respiratory compromise, pelvic obliquity, and poor sitting balance. Surgical stabilization of the spine is an effective technique for correcting deformity and restoring sitting posture. The decision to operate in this group of patients is challenging. Objectives The ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 23 publications
0
9
0
1
Order By: Relevance
“…For seach (4), 116 items were found, and 26 items were identified as relevant (Aghdasi et al 2020 ; Bettany-Saltikov et al 2015 , 2016 ; Cho et al 2014 ; Drazin et al 2011 ; Evaniew et al 2015 ; Figueiredo et al 2016 ; Guan et al 2020 ; Hawes & O’Brien 2008 ; Kim et al 2012 ; Larson et al 2013 ; Lau et al 2014 ; Ledonio, Polly & Crawford 2013 ; Legg et al 2014 ; Liang et al 2012 ; Sharma et al 2013 ; Theis, Gerdhem & Abbott 2015 ; Toovey et al 2017 ; Weiss 2008 ; Weiss & Goodall 2008a , 2009 ; Wu et al 2019 ; Yadla et al 2010 ; Yang et al 2016 ; Yoshihara 2019 ; Zanirato et al 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For seach (4), 116 items were found, and 26 items were identified as relevant (Aghdasi et al 2020 ; Bettany-Saltikov et al 2015 , 2016 ; Cho et al 2014 ; Drazin et al 2011 ; Evaniew et al 2015 ; Figueiredo et al 2016 ; Guan et al 2020 ; Hawes & O’Brien 2008 ; Kim et al 2012 ; Larson et al 2013 ; Lau et al 2014 ; Ledonio, Polly & Crawford 2013 ; Legg et al 2014 ; Liang et al 2012 ; Sharma et al 2013 ; Theis, Gerdhem & Abbott 2015 ; Toovey et al 2017 ; Weiss 2008 ; Weiss & Goodall 2008a , 2009 ; Wu et al 2019 ; Yadla et al 2010 ; Yang et al 2016 ; Yoshihara 2019 ; Zanirato et al 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…High rates of early complications have been found mainly in surgery applied for paediatric deformities as well as for adult deformities (Cho et al 2014 ; Drazin et al 2011 ; Figueiredo et al 2016 ; Fu at al. 2016 ; Guan et al 2020 ; Hawes & O’Brien 2008 ; Kim et al 2012 ; Ledonio et al 2013 ; Legg et al 2014 ; Sharma 2013 ; Toovey et al 2017 ; Wu et al 2019 :682–693; Yadla et al 2010 ; Zanirato et al 2018 ). In the systematic review by Zanirato et al ( 2018 ), the rate of complications for patients with adult spine deformity (ASD) is dependent on the surgical technique applied, between 24% and 36% perioperative plus 11% and 15% late complications.…”
Section: Resultsmentioning
confidence: 99%
“…reported that 3.5% (7/199) of patients with CP in GMFCS level V died within 2 years after spinal surgery. In a systematic review of patients with CP undergoing spinal surgery, Legg et al 26 . observed morality rates of 2.8% to 19% from less than 1 year to 8 years 7 months after spinal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a systematic review conducted by Legg et al 12 reported that the overall complication rate after spinal fusion at the last follow-up in pediatric patients with CP ranged from 10.9% to 70.9%. Infections and surgical site infection (SSI) were the most prevalent postoperative complications encountered 12 …”
mentioning
confidence: 99%